(3BdjGJ GdTQcGJ dJMSjf GdeQGcR GdJfGaSjIs - (3aQjO(B, (3GdfLGQs ((3GdEScfOQjI(B:s (3eDSSI THGH GdLGeYI(B,s, 2006)
(3JMdjd ehba GdefGaSI hGdJfGaSjI(B- (3JMdjd GdaQU GdJShjbjI(B- (3GdegGQGJ GdESJQGJjLjI(B- (3GdJQhjM hGdGJUGdGJ GdJShjbjI(B- (3GSJQGJjLjGJ GdYdGbGJ GdYGeI hGdJQhjL(B- (3HMhK GdYdGbGJ GdYGeI hbjGS GdBQGA(B- (3CSGdjH GdJMdjd GdJfGaSj hGdCReGJ(B- (3eONd GdebGQGfGJ GdJWhQjI GdeSJeQI dJMSjf GdeQGcR GdJfGaSjIs
Keywords: (3GdJQhjLs; (3GdefGaSIs